Ethnicity-related stereotypes and their impacts on medical students: A critical narrative review of health professions education literature. (2nd September 2022) - Bandyopadhyay, Soham; Boylan, Conor T.; Baho, Yousif G.; Casey, Anna; Asif, Aqua; Khalil, Halimah; Badwi, Nermin; Patel, Rakesh
Abstract: Background: Stereotypes are oversimplified beliefs about groups of people. Social psychology concepts and theories describing ethnicity-related stereotypes are well reported in non-medical educational settings. In contrast, the full impact of stereotyping on medical students, and the extent to which they were represented in health professions education (HPE) is less well-described. Using the lens of social psychological theory, this review aimed to describe ethnicity-related stereotypes about medical students portrayed in HPE literature and the impacts of those stereotypes. Methods: A critical narrative approach was undertaken. Social psychology concepts and theories were used as a framework through which to review the impacts of ethnicity-related stereotypes on medical students as described in HPE literature. A database search of Ovid MEDLINE, JSTOR, Project Muse, and PsychINFO was conducted to identify both theoretical and empirical articles relating to this topic in the HPE literature. Data was synthesised using thematic analysis, giving particular care to appraise the evidence from perspectives in social psychology. Findings: In HPE, the experiences and impact of stereotyping on learners from minority ethnic groups was explained by social psychology concepts such as stereotype threat, stereotype reactance, attributional ambiguity, self-fulfilling prophecy, stereotype boost, stereotype lift, and stereotype masking. Stereotype boost and stereotype lift were particularly described among students who identified as White, whereas stereotype threat was described more commonly among students from minority ethnics groups. The impact of stereotyping is not just on assessment, but may be across all teaching and learning activities at medical school. Interpretation: Social psychology concepts and theories can be used to describe the experience and impact of ethnicity-related stereotypes in HPE. Educators can better support learners from minority ethnic groups by self-reflecting over assumptions about individuals from minority ethnic groups, as well as minimise the impact of stereotyping and bias to create more inclusive learning environments.